2013
DOI: 10.1097/aln.0b013e31829c3029
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Volume and Survival in Closed Intensive Care Units Is Weak and Apparent Only in Mechanically Ventilated Patients

Abstract: In the currently studied healthcare system characterized by 24/7 intensivist coverage, the authors found wide variability in outcome among ICUs even after adjusting for severity of illness but no relationship between ICU volume and outcome. Only mechanically ventilated patients in very low-volume centers had slightly worse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…A relationship between high volume and better outcome was reported in the EURICUS I database [ 37 ], for some high-risk surgical patients [ 38 ] and ICU cancer patients with septic shock [ 39 ], and a systematic review [ 40 ] confirmed this finding. Nevertheless, the volume-outcome relationship has been questioned [ 41 ] and a recent study found no correlation between standardized mortality ratio and ICU volume with only mechanically ventilated patients in very low-volume centres [ 42 ]. However, in our study we adjusted hospital mortality also for the size of the hospitals, which was strongly related to the volume of activity.…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between high volume and better outcome was reported in the EURICUS I database [ 37 ], for some high-risk surgical patients [ 38 ] and ICU cancer patients with septic shock [ 39 ], and a systematic review [ 40 ] confirmed this finding. Nevertheless, the volume-outcome relationship has been questioned [ 41 ] and a recent study found no correlation between standardized mortality ratio and ICU volume with only mechanically ventilated patients in very low-volume centres [ 42 ]. However, in our study we adjusted hospital mortality also for the size of the hospitals, which was strongly related to the volume of activity.…”
Section: Discussionmentioning
confidence: 99%
“…An expansive body of literature demonstrates the volume-outcome relationship in a number of medical conditions, operations, and procedures. 6,[12][13][14][15][16][17][18][19][20] Consensus guidelines exist regarding threshold numbers for institutional competency of both total and primary PCI, pointing toward worse outcomes below these recommended thresholds. 14,21,22 This relationship has not been explored for patients with CS.…”
mentioning
confidence: 99%
“…These may be key aspects that allow these level III ICUs to adequately care for sicker patients. Similar to the article by Kluge and colleagues [3], some previous publications have questioned the volume- [1]. Some of these variables were known in this study and included in the models while others remain unknown or are estimates.…”
mentioning
confidence: 61%
“…The strongest associations are found when the task or treatment is high risk or of high complexity. In trauma surgery, percutaneous coronary interventions in myocardial infarction, and many high-risk surgical procedures such a correlation between volume and outcome has been established [1]. It is very tempting to assume that such a volume-outcome relationship does exist for intensive care units (ICUs) as well, which combine both high risk and high complexity.…”
mentioning
confidence: 99%